TEMA REVOLUSI MENTAL DALAM PERSPEKTIF AL QURAN - Sulaiman Mohammad Nur (Jurnal Studi Agama, 2019)
This paper examines mental revolution which is interpreted as a fundamental change in the mindset of people who master the context of life, both daily life and the life of nation and state, the idea of mental revolution is more studied from a political, economic, social, cultural and educational perspective , and much more. Keywords: mental revolution, Al Quran